Derm-ographics: The Australian Dermatologist and Social Media - Antonia C Rowson; Saskia J Rowson (JMIR Dermatology, 2023)
Social media significantly affects how patients understand their health and choose their healthcare providers, yet Australian dermatologists have a limited online presence compared to their global peers.